Non-linear dynamics of human locomotion: effects of rhythmic auditory cueing on local dynamic stability - Terrier, Philippe; Dériaz, Olivier (Frontiers in Physiology, 2013)
It has been observed that times series of gait parameters (stride length (SL), stride time (ST) and stride speed (SS)), exhibit long-term persistence and fractal-like properties. Synchronizing steps with rhythmic auditory stimuli modifies the persistent fluctuation pattern to anti-persistence. Another nonlinear method estimates the degree of resilience of gait control to small perturbations, i.e. the local dynamic stability (LDS). The method makes use of the maximal Lyapunov exponent, which estimates how fast a nonlinear system embedded in a reconstructed state space (attractor) diverges after an infinitesimal perturbation. We propose to use an instrumented treadmill to simultaneously measure basic gait parameters (time series of SL, ST and SS from which the statistical persistence among consecutive strides can be assessed), and the trajectory of the center of pressure (from which the LDS can be estimated). In 20 healthy participants, the response to rhythmic auditory cueing (RAC) of LDS and of statistical persistence (assessed with detrended fluctuation analysis (DFA)) was compared. By analyzing the divergence curves, we observed that long-term LDS (computed as the reverse of the average logarithmic rate of divergence between the 4th and the 10th strides downstream from nearest neighbors in the reconstructed attractor) was strongly enhanced (relative change +47%). That is likely the indication of a more dampened dynamics. The change in short-term LDS (divergence over one step) was smaller (+3%). DFA results (scaling exponents) confirmed an anti-persistent pattern in ST, SL and SS. Long-term LDS (but not short-term LDS) and scaling exponents exhibited a significant correlation between them (r=0.7). Both phenomena probably result from the more conscious/voluntary gait control that is required by RAC. We suggest that LDS and statistical persistence should be used to evaluate the efficiency of cueing therapy in patients with neurological gait disorders.